E-Learning as a Core Component of the Instructional Design Profession - Martinez, Tome Raymond; Cummins, Paula; Savenye, Wilhelmina; Shewell, Justin (International Journal of Advanced Corporate Learning (iJAC), 2012)
Periodic assessment and evaluation is an important part of any successful program. This paper presents the findings of a needs assessment which examined the influence of e-learning and technical skill development in the area of educational technology with specific attention paid to the field of instructional design. A three-phase mixed methods approach was employed to carryout this assessment. Findings indicate that there is a strong perception among the participants that e-learning is a core component of the instructional design profession. The results of the study give a clear indication that e-learning is a significant influence on current instructional design operations. Therefore, it is necessary for students to acquire the skills required to successfully operate these programs. Recommendations were developed that can allow programs to be more responsive to current trends impacting the profession.